Relationship between leadership and coaching: a study on evulation of workers to their leaders - Koç, Ümit Hayri (My University, 2010)
Gelişen dünyada, bireylerin önemi ve üretim ve kalitedeki rolleri son otuz yılda daha da önemli olmuştur. Günümüzde, bu alanda pek çok akademik araştırma yapılmaktadır ve liderliğin önemine vurgu yapılmaktadır. Pek çok lider geliştirme programları tasarlanmaktadır ve bunların çoğu birey ve lider adaylarının iletişim becerileri üzerine odaklanmıştır. Bu becerilerden ikisi koçluk ve mentörlük becerileridir. Bu iki kavram, bu alanda çalışan yeni akademisyenler tarafından araştırıla gelmektedir. Pek çok uluslararası dergi de bu konular üzerinde durmaktadır. Öte yandan, lider adaylarının sahip oldukları koçluk ve mentörlük becerileri üzerinde yapılan yeterli çalışma mevcut değildir. Bu nedenle, bu araştırmada liderlerin koçluk becerilerinin liderlik özellikleri üzerindeki rolüne değinilmiştir. Sonuçlara göre koçluğun liderlik ile pozitif ilişkisi olduğu görülmüştür. THE RELATIONSHIP BETWEEN LEADERSHIP AND COACHING: A STUDY ON EVALUATION OF WORKERS TO THEIR LEADERS In the developing world, importance of individuals and their role at production and quality have been more important in last three decades. Nowadays, many academical researches on this field have been performed, and the importance of leadership has been expressed. Many leader development programs are designed and many of them are focused on human and communication skills of leader candidates. Two of these skills are coaching and mentoring. These two concepts are being researched by new academicians working on management area. Many international journals also are focusing on these concepts. On the other hand, it has been found that there have not been enough researches on the effects of coaching and mentoring that leader candidates have on their leadership. For this reason, in this research, the roles of coaching on leadership skills were researched. According to results, it was found that coaching skills have positive relation with leadership.
Keywords: Koçluk; Liderlik; Liderlik Davranışı